2011
DOI: 10.1007/s10295-011-0990-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a xylose reductase gene in the xylose metabolic pathway of Kluyveromyces marxianus NBRC1777

Abstract: Kluyveromyces marxianus is thermotolerant yeast that is able to utilize a wider range of substrates and has greater thermal tolerance than most other yeast species. K. marxianus can assimilate xylose, but its ability to produce ethanol from xylose in oxygen-limited environments is poor. In the present study, the K. marxianus xylose reductase (KmXR) gene (Kmxyl1) was cloned and the recombinant enzyme was characterized to clarify the factors that limit xylose fermentation in K. marxianus NBRC1777. KmXR is a key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 38 publications
0
34
0
Order By: Relevance
“…When the translated polypeptide sequence of XR from K. marxianus ATCC 36907 was compared with other reported XR sequences, a putative active site signature ( 265 IPKS 268 ) was shown [3]. When XR sequence from K. marxianus ATCC 36907 was compared with that from K. marxianus NBRC 1777 which was already reported [26], they are almost similar except three amino acids (Fig. 2).…”
Section: -Fmel1mentioning
confidence: 85%
See 1 more Smart Citation
“…When the translated polypeptide sequence of XR from K. marxianus ATCC 36907 was compared with other reported XR sequences, a putative active site signature ( 265 IPKS 268 ) was shown [3]. When XR sequence from K. marxianus ATCC 36907 was compared with that from K. marxianus NBRC 1777 which was already reported [26], they are almost similar except three amino acids (Fig. 2).…”
Section: -Fmel1mentioning
confidence: 85%
“…Therefore, K. marxianus 36907-FMEL1 exhibited almost similar NADH-linked and NADPH-linked XR activities. XRs from K. marxianus ATCC 36907 and K. marxianus 36907-FMEL1 exhibited cofactor affinity to both NADPH and NADH while the XR from K. marxianus NBRC1777 was reported to display affinity only to NADPH as a cofactor and no affinity to NADH [26]. In the previous study, XR from K. marxianus NBRC1777 was expressed using Escherichia coli for enzymatic assays.…”
Section: Discussionmentioning
confidence: 98%
“…The motif was well-conserved among xylose reductase of several yeast strains except for CpXR of C. parapsilosis which Lys residue was substituted with Arg and resulting in preferentially used NADH as coenzyme 54 . The CtrXR that showed the highest sequence homology to those of A26XR was previously reported as NADPH-specific XR 14,17 . This result suggested that xylose reductase of C. tropicalis A26 might specify for an NADPH coenzyme, however, the expression of the xyl clone including the characterization of xylose reductase expressed is required.…”
Section: Cloning Of C Tropicalis A26 Xylose Reductase Genementioning
confidence: 81%
“…Comparison the obtained partial amino acid sequences of C. tropicalis A26 to those of other yeast strains in Gene Bank database revealed that C. tropicalis A26 xylose reductase possessed 98.4%, 78.5%, and 77.5% identity and 99.0%, 86.4%, and 85.9% similarity to xylose reductase of CtrXR of C. tropicalis (ABX60132C), CtXR of C. tenuis (AAC25601), and CsXR of C. shehatae (ABK35120), respectively (Table 4). Amino acid sequence alignment of the partial xylose reductase revealed tetra amino acid motif (Ile-Pro-Lys-Ser), an NAD(P)H species motif 14,17,53 ( Fig. 2).…”
Section: Cloning Of C Tropicalis A26 Xylose Reductase Genementioning
confidence: 99%
See 1 more Smart Citation